The challenges and molecular approaches surrounding interleukin-2-based therapeutics in cancer. Issue 1 (March 2019) - Tang, Anthony; Harding, Fiona
Highlights: IL2-based cancer therapies are limited by their toxicity and pleiotropy. Current engineering approaches target IL2 half-life and cell/receptor specificity. IL2 may enhance the efficacy of checkpoint inhibitors and CAR-T-based therapies. Abstract: Interleukin-2 has had a long history as a promising cancer therapeutic, being capable of eliciting complete and durable remissions in patients with metastatic renal cell carcinoma and metastatic melanoma. Despite high toxicity and efficacy limited to only certain patient subpopulations and cancer types, the prospective use of novel, engineered IL2 formats in combination with the presently expanding repertoire of immuno-oncological targets remains very encouraging. This is possible due to the significant research efforts in the IL2 field that have yielded critical structural and biological insights that have made IL2 more effective and more broadly applicable in the clinic. In this review, we discuss some of the molecular approaches that have been used to further improve IL2 therapy for cancer.